A Framework to Incentivise Green Networks and Infrastructure in the 6G Mobile Ecosystem - Santiago Andrés Azcoitia; Sergio Illescas Cabiró; Zoraida Frías Barroso (International Telecommunications Society (ITS), 2025)
The transition to greener energy sources and the reduction of greenhouse gas (GHG) emissions are essential to mitigating climate change and ensuring a sustainable future. Although the ICT sector currently accounts for a modest share of global emissions, its contribution is expected to soar due to the rapid growth in data and computing demand in all industry verticals, driven by the deployment of 6G that will enable AI-driven services by providing ultra-reliable, low-latency, and high-capacity connectivity across the cloud–edge continuum. Initiatives like 6Green are developing technical capabilities to measure and expose information on GHG emissions associated with 6G network services throughout the value chain. However, such technical enablers are not sufficient to incentivise investment in sustainable infrastructures and the adoption of green services. This paper introduces a techno-economic framework to evaluate policy mechanisms for promoting greener network and infrastructure in the 6G ecosystem. The model captures interactions between stakeholders under varying market conditions, integrates sustainability key performance indicators (KPIs), such as carbon emissions, and operationalises the concept of Decarbonisation Level Agreements (DLAs) as an extension of traditional Service Level Agreements (SLAs). Four policy options are compared: laissez-faire, infrastructure subsidisation, uniform DLA enforcement, and a tiered DLAs allowing for green premium services. Results show that while strict DLAs and subsidies can reduce emissions, they may also introduce cost and capacity constraints unless carefully designed. Tiered approaches, which combine regulation with market-driven incentives and user awareness, offer a more balanced and scalable path toward sustainability.
Keywords: 330; Mobile networks; 6G; economics; sustainability